Harnessing Solar Energy to meet Energy needs for water desalination in Gaza Strip - Khatib, Imad (J. of Applied Sciences in Environmental Sanitation, 2008)
Water and sanitation conditions in Gaza Strip are facing severe problems in addition to poor conditions of existing municipality infrastructure that adversely affect the local environment, the ecological systems and the public health. The lack of power systems has, in the past two years, lead to polluting the coastal aquifer, which is the only water resources that Gaza Strip has,with untreated wastewater and the intruded seawater. A creative solution is presented by which a local technology could be used in addition to utilizing the available solar energy for providing the proper thermal and electrical needed. The proposed solution is based on the direct contact membrane desalination technology operated by solar energy conversion system. The conversion system uses evacuated tubes solar collectors for providing the thermal energy needed and photovltaic solar modules for providing the needed electrical power. System components' optimized size area are also presented.
Keywords: Energy Status, water resources, membrane desalination, solar collectors, photovoltaic solar modules